Gerakan Literasi Sekolah: Sumber Literasi Keagamaan untuk Pendidikan Agama Katolik - Jelahu, Timotius Tote; Aprianto, Dicky (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2024)
The Catholic Church has the authority to determine and oversee the content of the Catholic Religious Education curriculum. In alignment with the broader literacy movement in schools, it is essential that the materials used for religious literacy adhere to the doctrinal teachings of the Catholic Church. This study examines the key sources that must be considered when preparing materials for Catholic Religious Education in schools, focusing specifically on religious literacy. This qualitative research draws on existing literature, including previous studies and relevant documents. The findings suggest that Catholic Religious Education is inherently intertwined with theological reflection. As a component of theology, Catholic Religious Education provides a vital space for faith reflection, thereby contributing to the enhancement of Catholic religious literacy. In this context, the literacy movement within Catholic Religious Education must prioritize the foundational sources of the Catholic faith: Sacred Scripture, Sacred Tradition, and the teachings of the Magisterium. Additionally, the learner’s lived context should be recognized as an indispensable source, as it plays a crucial role in shaping their understanding of the faith.